The impact of HIV couple testing and counseling on social support among pregnant women and their partners in Lilongwe, Malawi: an observational study. Issue 2 (1st February 2019) - Bhushan, Nivedita L.; Golin, Carol E.; McGrath, Nuala; Maman, Suzanne; Tsidya, Mercy; Chimndozi, Limbikani; Wesevich, Austin; Hoffman, Irving F.; Hosseinipour, Mina C.; Miller, William C.; Rosenberg, Nora E.
ABSTRACT: Couples HIV testing and counseling (couple counseling) promotes safer sexual behaviors, increases communication between couples, and decreases HIV transmission. However, the impact of couple counseling on social support, critical for persons living with HIV, has not been examined. Ninety couples with a recently tested HIV-positive pregnant woman (female-positive couples) and 47 couples with a recently tested HIV-negative pregnant woman (female-negative couples) were enrolled in an observational study at an antenatal clinic in Malawi. Each couple member was assessed immediately before and one month after couple counseling for partner, family, and peer social support using the Multidimensional Scale of Perceived Social Support. Before couple counseling, social support was lower among women than men in both female-positive couples ( β  = −10.00, p  < .01) and female-negative couples ( β  = −8.43, p   < .01). After couple counseling, social support increased for women in female-positive couples ( β  = 4.01, p  < .01) and female-negative couples ( β  = 4.69, p  < .01) but not for men in either type of couple. Couple counseling could be an effective strategy to increase social support for women, including those with recent HIV diagnoses.